Massive release of natural hydrogen from a geological seep (Chimaera, Turkey): Gas advection as a proxy of subsurface gas migration and pressurised accumulations. (22nd March 2023) - Etiope, Giuseppe
Abstract: Subsurface geological reservoirs of natural hydrogen gas (H2 ), a clean fuel and energy vector, are currently a target for energy resource exploration. Such reservoirs can be revealed by the presence of H2 within soil, analogous to hydrocarbon seepage in petroleum systems. Nevertheless, defining the level of soil H2 that can indicate a potentially economic resource is currently impossible, and identifying geological H2 within soil-gas is challenging because H2 concentrations and the isotopic composition (δ 2 H) may overlap with the in-situ biological signature. In spite of these limitations, analogies to conventional hydrocarbon systems suggest that the presence of surface advective gas flows can reveal (unlike diffusion) a subsoil source and even pressurised gas accumulations of H2 . Here, a massive release of H2 is reported from a CH4 –H2 rich seep in Turkey, known as Chimaera, an emblematic example of H2 advection. The site represents the first case where a closed-chamber flux method was applied for H2 seepage. H2 advection at the site was clearly indicated by numerous gas vents and flames, and by the heterogeneous spatial distribution of pervasive, invisible exhalation (miniseepage), inducing rapid H2 concentration build-up within the chamber. H2 emission (∼10 ± 3 kg day −1, with the highest H2 emission factor reported, thus far, of ∼5000 kg km −2 day −1 ) is continuous and long lasting (flames have been documented for millennia) and, using an analogy for hydrocarbon seeps, may stem from pressurised accumulations. The Chimaera case is illustrative of how detecting soil H2 advection may help unravel surface (biological) vs. subsoil (geological) gas origins in cases where, in the absence of significant gas seepage, soil H2 concentrations are within the range of biological production (10 0 -10 3 ppmv, e.g., as for "fairy circles" observed in several countries). Interpretations must, however, be supported by additional geochemical data and evaluations of potential biological H2 production within the surface ecosystem. Highlights: First direct measurements of natural H2 flux from a seep using a closed-chamber technique. Highest geological H2 emission factor reported to date. Soil H2 advection as a potential proxy of subsurface gas migration and reservoirs.